COMPARISON OF EXAMINATION OF SODIUM ELECTROLYTE LEVELS IN SERUM USING RED CAP VACUUM TUBES AND YELLOW CAP VACUUM TUBES AT TOTO KABILA HOSPITAL BONE BOLANGO DISTRICT - Sri Tinsia Husain Husain; Diah Astini Paramita; Gayatri D. Soga (LPPM Universitas Bina Mandiri Gorontalo, 2022)
Sodium is an essential nutrient for maintaining blood volume, regulating water balance in cells and maintaining nerve function. Sodium examination generally uses serum as a specimen. Serum is a liquid component of blood that no longer contains blood cells and clotting factors. The purpose of this study was to compare the results of examining sodium electrolyte levels in serum using a red-covered vacuum tube and a yellow covered vacuum tube at Toto Kabila Hospital, Bone Bolango Regency. The method in this study uses a quantitative approach with a descriptive type of research. The sampling technique used in this study was purposive sampling with a total sample of 30 patients. Comparison ResultsExamination of sodium electrolyte levels in serum using a red lid vacuum tube and a yellow lid vacuum tube contained 9 Normal Samples and 21 Abnormal Samples with the Mann-Whitney Test results showing that the significant value was > 0.05 or P = 0.312, so it can be concluded that there was no the difference between the red cap vacuum canister and the yellow cap vacuum canister.